Sintesis Asil Gliserol Melalui Reaksi Esterifikasi Asam Oleat dengan Gliserol - Husada, Caesar Purnama; Sulistyo, Hary; Sediawan, Wahyudi Budi (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Acyl glycerol derivatives from oleic acid, especially monoacylglycerol (MAG) and diacylglycerol (DAG), are products that is widely used in the food, lubricant, and cosmetic industries. Acyl glycerol can be obtained through esterification reaction of glycerol with fatty acids.  This study aims to determine the effect of temperature on the conversion and amount of acyl glycerol produced. This research was conducted using a batch system with temperature variations of 80°C, 100°C, and 120°C with HCl 1%wt as catalyst and 1:1 reactant mole ratio (glycerol: oleic acid) for 2 hours reaction time. Samples were taken every 10 minutes, then the samples were analyzed using Thin Layer Chromatography (TLC) to determine the fraction of the product produced. The experimental results showed that increasing the temperature will produce higher conversions and acyl glycerols. The highest conversion of oleic acid occurred at 120°C (43.016%), with mole percentage of 1,796% monoacylglycerol (MAG), 3,820% diacylglycerol (DAG), and 5,813% triacylglycerol (TAG).